Intracellular Uptake Mechanism of Lutein in Retinal Pigment Epithelial Cells - Yuki Sato; Yu Kondo; Masato Sumi; Yoh Takekuma; Mitsuru Sugawara (Frontiers Media S.A., 2013)
Purpose. Lutein is a carotenoid mainly found in green leafy vegetables and is located in the macula lutea in the human eye. It has received much attention recently due to its preventive effect on age-related macular degeneration, and it has been consumed as a supplement. However, little information about the pharmacokinetic properties of lutein is available. Detailed knowledge of pharmacokinetic properties of lutein is needed for the development of pharmaceutics. In this study, we focused on the macular accumulation of lutein and investigated the uptake mechanism into human retinal pigment epithelial cells. Methods. ARPE-19 cells were used for the study on the accumulation mechanism of lutein. The concentration of lutein was determined using an HPLC system. Involvement of scavenger class B type 1 (SR-B1) in the accumulation of lutein in ARPE-19 cells was suggested from the results of an inhibition study using block lipid transport 1 (BLT-1), a selective inhibitor of SR-B1. To investigate the involvement of SR-B1 in more detail, small interfering RNA (siRNA) was transfected and the mRNA and protein expression levels of SR-B1 were assessed by quantitative real-time reverse transcription polymerase chain reaction and Western blotting, respectively. Results. We confirmed a sufficient siRNA knockdown effect in both mRNA and protein expression levels of SR-B1. We then found that lutein uptake was significantly decreased by siRNA knockdown of SR-B1. Conclusion. The uptake of lutein was significantly decreased by 40% compared with the control uptake level. This suggested that active transport of lutein into ARPE-19 cells is mainly via SR-B1, given the result that lutein uptake at 4ºC was about 40% less that that at 37ºC.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.